(untitled) (Confluenţe Bibliologice, 2019)
This article discusses the accomplishment of the mission of reference librarians in informational assistance, guidance, orientation of users in order to provide with traditional informational resources (solving simple problems with the help of encyclopedias and dictionaries, consulting bibliographies for more complicated problems) and providing electronic multi-aspect services in collecting the necessary information, as well as consulting / intermediation in order to involve the user in the process of searching, selec ting and ﬁnding information, thus contributing to the formation of the information culture.